Enemies or allies? How NGOs can push the military towards transparency around the use of force. (16th June 2022) - Colli, Francesca; Reykers, Yf
Abstract: This article examines the conditions under which non-governmental organisations (NGOs) gain access to defence administrations when campaigning for transparency around the use of military force. We theorise that gaining access in this traditionally secluded domain is a matter of supply and demand. NGOs can gain access through technical and political information, yet not without demand for these resources, dependent on the politicisation of concerns about the use of force. We focus on the activities of Airwars, an international NGO, and its campaign in the Netherlands (2015–20) to foster transparency about civilian casualties caused by Dutch airstrikes. Our analysis shows that their credible information about air strikes led to access to the defence administration and allowed them to effectively advocate for transparency, mediated by the politicisation of the issue through parliamentary and media attention. Our findings contribute both to the literature on NGO advocacy and to the field of civil-military relations.